Association between tumor size and prognosis in bladder cancer: novel classifications and insights from a SEER database analysis - Jia, Yige; Wu, Kan; Li, Xiang (Frontiers in Surgery, 2024)
ObjectiveAlthough tumor size is an essential oncologic feature, it is often underutilized in diagnosing and treating bladder cancer (BC). This study investigates the relationship between tumor size and BC prognosis, aiming to enhance clinical applications.MethodsBC patients were identified from the Surveillance, Epidemiology, and End Results (SEER) database (2004–2015). Cox proportional hazard models were conducted to identify prognostic factors, and restricted cubic splines (RCS) were used to assess the relationship between tumor size and survival outcomes. The Kaplan-Meier method and multivariate COX models were utilized to estimate the effect of the classification scheme.ResultsA total of 69,478 patients with BC were evaluated from the SEER database. Larger tumor size, recent diagnosis, older age, high pathologic grade, variant histology, advanced T stages, positive lymph node status, and receipt of radiotherapy and chemotherapy were associated with worse overall and cancer-specific survival. RCS curves of each stage showed that the relationship between tumor size and prognosis was non-linear. Optimal cut-off points were identified based on the shape of RCS curves, suggesting new classifications of tumor size: 2.5 cm and 5 cm for Ta, 3 cm and 5 cm for T1, and 4 cm and 6 cm for T2.ConclusionsIncorporating tumor size into prognostic evaluations can enhance bladder cancer risk stratification. Further research is needed to validate these findings and improve personalized treatment strategies.